Tutkimus- ja opetushenkilökunnan määräaikaiset työsuhteet suomalaisissa yliopistoissa - Kallio, Tomi J.; Kallio, Kirsi-Mari (Hallinnon tutkimuksen seura, 2023)
Fixed-term employments among academic personnel at Finnish universities This study focuses on fixed-term employments in Finnish universities. The relative amount of fixed-term employments in different career phases, universities and fields are described. The analyses reveal that the fixed-term employments are considerably more common in universities than in other areas of the labor market. While 71,7% of the Finnish scholars are in fixed-term employments, the equivalent number in the Finnish labor market in total is 14,9%. The role and nature of fixed-term employments in the Finnish academia is further discussed and it is suggested that the transition from the previous to the new career model divides the fixed-term employees into more fortunate and less fortunate ones. The tenure-track assistant and associate professors seem to be favored by of the new career system while the rest of the fixed- term employees seem less fortunate.
Keywords: fixed-term employments; university; career; academic precariat; fi=Henkilöstöjohtaminen|en=Human Resource Management|